2008
DOI: 10.1590/s0034-72992008000600006
|View full text |Cite
|
Sign up to set email alerts
|

Ototoxicidade e otoproteção em orelha interna de cobaias utilizando gentamicina e amicacina: aspectos ultra-estruturais e funcionais

Abstract: A ototoxicidade ainda é um desafio para medicina. A descoberta dos mecanismos endógenos autoprotetores das células ciliadas externas associados a métodos de avaliação funcional e ultra-estrutural das mesmas abriu nova perspectiva no entendimento e controle destes mecanismos. OBJETIVO: O trabalho objetivou determinar se subdoses de gentamicina protegia contra ototoxicidade da amicacina baseado nestes mecanismos e determinar se a amplitude das emissões otoacústicas teria correlação com grau de integridade das cé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…Structural changes were more intense in the first OHC row, followed by the second row. 26 These findings concur with those of other researchers, 18 who showed that aminoglycosides cause injury to the Corti organ mostly in OHC, where the progression of injury is from the cochlear base to its apex; the first OHC row is injured first, followed by the second and third rows in turn.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Structural changes were more intense in the first OHC row, followed by the second row. 26 These findings concur with those of other researchers, 18 who showed that aminoglycosides cause injury to the Corti organ mostly in OHC, where the progression of injury is from the cochlear base to its apex; the first OHC row is injured first, followed by the second and third rows in turn.…”
Section: Discussionsupporting
confidence: 92%
“…The morphological analysis of the injuries encountered in this study showed that the predominating changes were the absence and "V"-type deformities of stereociliae, which is similar to findings in other studies. 15,17,26 The presence of the vestibulocochlear structural changes we found in the present study confirm that the organophosphorus agrochemical is toxic; this had previously been commented only in relation to altered function of the auditory and vestibular systems.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations